Download
solving systems of equations using substitution n.
Skip this Video
Loading SlideShow in 5 Seconds..
Solving Systems of Equations using Substitution PowerPoint Presentation
Download Presentation
Solving Systems of Equations using Substitution

Solving Systems of Equations using Substitution

90 Vues Download Presentation
Télécharger la présentation

Solving Systems of Equations using Substitution

- - - - - - - - - - - - - - - - - - - - - - - - - - - E N D - - - - - - - - - - - - - - - - - - - - - - - - - - -
Presentation Transcript

  1. Solving Systems of Equations using Substitution

  2. Solving Systems of Equations using Substitution Steps: 1. Solve one equation for one variable (y= ; x= ; a=) 2. Substitute the expression from step one into the other equation. 3. Simplify and solve the equation. 4. Substitute back into either original equation to find the value of the other variable. 5. Check the solution in both equations of the system.

  3. y = 4x and 3x + y = -21 Step 1:Solve one equation for one variable. y = 4x(This equation is already solved for y.) Step 2: Substitute the expression from step one into the other equation. 3x + y = -21 3x + 4x = -21 Step 3: Simplify and solve the equation. 7x = -21 x = -3

  4. y = 4x 3x + y = -21 You found that x = -3 Step 4: Substitute back into either original equation to find the value of the other variable. (if x = -3 then y = ?) 3x + y = -21 3(-3) + y = -21 -9 + y = -21 y = -12 Solution to the system is (-3, -12).

  5. y = 4x 3x + y = -21 Step 5: Check the solution in both equations. Solution to the system is (-3,-12). 3x + y = -21 3(-3) + (-12) = -21 -9 + (-12) = -21 -21= -21 y = 4x -12 = 4(-3) -12 = -12

  6. Want

  7. x + y = 5 and y = 3 + x

  8. Example #2: x + y = 10 and 5x– y = 2 Step 1: Solve one equation for one variable. x + y = 10 y = -x +10 Step 2: Substitute the expression from step one into the other equation. 5x - y = 2 5x -(-x +10) = 2

  9. x + y = 10 and 5x– y = 2 Step 3: Simplify and solve the equation. 5x -(-x + 10) = 2 5x + x -10 = 2 6x -10 = 2 6x = 12 x = 2

  10. x + y = 10 and 5x– y = 2 You found that x = 2 Step 4: Substitute back into either original equation to find the value of the other variable. x + y = 10 2 + y = 10 y = 8 Solution to the system is (2,8).

  11. x + y = 10 5x – y = 2 Step 5: Check the solution in both equations. Solution to the system is (2, 8). 5x – y = 2 5(2) - (8) = 2 10 – 8 = 2 2 = 2 x + y =10 2 + 8 =10 10 =10

  12. Smart Bird

  13. Closure: Solve by substitution